2018
DOI: 10.1016/j.chiabu.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment in childhood and intimate partner violence: A latent class growth analysis in a South African pregnancy cohort

Abstract: Intimate partner violence (IPV) is a significant global problem, prevalent in low and middle-income countries (LMICs). IPV is particularly problematic during the perinatal and early postnatal period, where it is linked with negative maternal and child health outcomes. There has been little examination of profiles of IPV and early life adversity in LMIC contexts. We aimed to characterize longitudinal IPV and to investigate maternal maltreatment in childhood as a predictor of IPV exposure during pregnancy and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…Exposure to lifetime IPV in particular, was associated with differences in the infant and maternal faecal bacteria. IPV is a traumatic stressor that often occurs over prolonged and repeated episodes (63) and IPV during pregnancy often persists postpartum (64-66). It should be noted that other effects of IPV which were not controlled for in this study may contribute to its association with changes to infant faecal bacterial composition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to lifetime IPV in particular, was associated with differences in the infant and maternal faecal bacteria. IPV is a traumatic stressor that often occurs over prolonged and repeated episodes (63) and IPV during pregnancy often persists postpartum (64-66). It should be noted that other effects of IPV which were not controlled for in this study may contribute to its association with changes to infant faecal bacterial composition.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that other effects of IPV which were not controlled for in this study may contribute to its association with changes to infant faecal bacterial composition. For example, mothers who have experienced IPV are more likely to have weakened bonding with their infant (66, 67), which may in turn affect the infant faecal bacterial composition. Supporting evidence from animal work showed that male rat pups that were stressed by maternal separation had elevated faecal levels of Enterobacteria and Bacteroides during adulthood (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To narrow the search for this concept analysis, the focus is on personal resilience and more specifically on perinatal resilience. Research about resilience within the perinatal period has mainly focused on the presence of adversity or trauma such as intimate partner violence, teen-pregnancy and postpartum depression (Wilson-Mitchell et al, 2014;SmithBattle and Freed, 2016;Dekel et al, 2017;Barnett et al, 2018). Suspected components of resilience have been associated with improved perinatal outcomes, such as increased birth weight, decreased rates of postpartum depression, emotional stress and sleeping problems (Roos et al, 2013;Waugh and Koster, 2015;Hain et al, 2016;Johnson et al, 2018).…”
Section: Identifying Uses Of the Conceptmentioning
confidence: 99%
“…An increasing body of research focused on the identification of resilience-promoting characteristics and mechanisms, which can be beneficial for mental health outcomes (Schiele and Domschke, 2018). However, only a few studies assess resilience during the perinatal period, with most of them focusing on unusual trajectories with the presence of adversity or trauma such as intimate partner violence or teen pregnancy (Wilson-Mitchell et al, 2014;SmithBattle and Freed, 2016;Dekel et al, 2017;Barnett et al, 2018;Xuemei et al, 2019). Yet a definition of perinatal resilience is absent.…”
Section: Introductionmentioning
confidence: 99%